Robust evolutionary shape optimization for ergonomic excellence based on contact pressure distribution. Issue 13 (2nd October 2020) - Pehnec, Igor; Marinić-Kragić, Ivo; Vučina, Damir
Abstract: The aim of this paper is the development of a robust evolutionary shape optimization procedure for ergonomic excellence based on contact pressure distribution. FEM - based numerical analysis is implemented to obtain the resulting contact pressure distribution. An example of person-seat interaction is analysed in this paper since plenty of experimental data set exists on this topic. A simplified geometrical model of the human body and seat is used and partly parameterized using a generic B-spline surface. The impact of the changes in geometry on the pressure distribution is analysed by the optimizer, and the seat geometry is steered into a shape with minimal high contact pressure areas. The procedure is general and can be adapted (with changes in geometry and boundary conditions) to distinct ergonomic problems such as footwear, therapeutic beds, automotive or aeronautical seating. The developed procedure can aid in virtual testing during the seat development phase in cases when the seat is designed for a selected population or for a single person and expected postural variations.